PERAN LEMBAGA SWADAYA MASYARAKAT TERHADAP PROGRAM PENGELOLAAN HUTAN BERBASIS MASYARAKAT DALAM KONTEKS PEMBANGUNAN DAERAH - Riva, Wahyu Fathurrahman; Hutagaol, Parulian; Levang, Patrice (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2013)
The increasing rate of forest degradation and lack of local communities’ access to forest, have been a significant stimulus for the implementation of community-based forest management (CBFM). This study aims to assess and analyze the role of NGOs in the implementation of the CBFM program and formulate strategies to improve the role of NGOs in the implementation of the CBFM program. This study use two methods of analysis, which are analyzes the performance of NGOs in the CBFM program and analysis of the institutional development of local institutions. The results of this study, are: 1) Most of NGos (5 NGOs) have good performance in the implementation of the CBFM program funded by UNDP and 2 NGOs have good performance and less well. 2) Development of local institutions influenced by local resource conditions, international, national, and local political-economic factors, and local socio-political factors. 3) The strategy to increase the role of NGOs in the implementation of CBFM in the context of regional development can be done through several ways, are: development in institutional capacity of NGOs, development in empowerment and institutional capacity of community, development in advocacy of local government, development in business of community with the private sector.Keywords: Community-Based Forest Management, Non-Governmental Organizations, Strategy